Noise Radar Technology as an Interference Prevention Method - Gaspare Galati; Gabriele Pavan (Journal of Electrical and Computer Engineering)
In some applications, such as automotive and marine/navigation, hundreds of radars may operate in a small environment (e.g., a road complex or a strait) and in an allocated frequency band with limited width. Therefore, a compatibility problem between different radars arises that is not easily solved by time, frequency, space, or polarization diversity. The advent of fast digital signal processing and signal generation techniques makes it possible to use waveform diversity to solve this problem that will be exacerbated in the next future. Ideal waveforms for the diversity are supplied by Noise Radar Technology (NRT), whose application is promising in some military applications as well as in the civilian applications considered in this paper. In addition to being orthogonal as much as possible, the random signals to be transmitted have to satisfy requirements concerning side lobe level and crest factor, calling for novel, original design and generation processes.